Cannabis Use and Resting State Functional Connectivity in the Aging Brain - Watson, Karli K.; Bryan, Angela D.; Thayer, Rachel E.; Ellingson, Jarrod M.; Skrzynski, Carillon J.; Hutchison, Kent E. (Frontiers in Aging Neuroscience, 2022)
Several lines of evidence suggest that older adults (aged 65+) sharply increased their cannabis use over the last decade, highlighting a need to understand the effects of cannabis in this age group. Pre-clinical models suggest that cannabinoids affect the brain and cognition in an age-dependent fashion, having generally beneficial effects on older animals and deleterious effects on younger ones. However, there is little research on how cannabis affects the brains of older adults or how older adults differ from younger adults who use cannabis. Resting state functional connectivity (rsFC) measures provide sensitive metrics of age-related cognitive decline. Here we used seed-to-voxel and ROI-to-ROI approaches in the software package CONN to compare rsFC in older adults (60-88 years old) who are either regular users of cannabis (n=43) or nonusers (n=143). We found stronger connectivity between the hippocampus/parahippocampus and the anterior lobes of the cerebellum in older adult cannabis users relative to nonusers. A similar pattern of strengthened connectivity between hippocampal and cerebellar structures was also present in 25-35 year old nonusers (n=23) in comparison to older nonusers. These findings suggest that future studies should examine both the potential risks of cannabinoids, as well as a potential benefits, on cognition and brain health for older adults.